2016
DOI: 10.1108/itp-05-2014-0100
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of influencing factors on the IPTV subscription

Abstract: Purpose – The purpose of this paper is to examine how user-perceived video quality, measured by computer assisted web survey, interacts with content richness (CR) and interactivity (IA). It also analyzes how those internet protocol television (IPTV) idiosyncrasies impacts audience perceptions (perceived usefulness (PU) and perceived resistance (PR)) and actual subscriptions. Design/methodology/approach – A computer assisted web survey wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 58 publications
2
5
1
2
Order By: Relevance
“…Essentially, the higher the perceived usefulness by consumers, the more pronounced their willingness to extend their subscriptions. This observation aligns with findings from studies conducted by Park et al (2016), Gunawan (2022), and Kang et al (2014).…”
Section: Wwwjournalmabisorg 15supporting
confidence: 91%
See 1 more Smart Citation
“…Essentially, the higher the perceived usefulness by consumers, the more pronounced their willingness to extend their subscriptions. This observation aligns with findings from studies conducted by Park et al (2016), Gunawan (2022), and Kang et al (2014).…”
Section: Wwwjournalmabisorg 15supporting
confidence: 91%
“…The diversity in media content, as elucidated by Park et al (2016), can positively impact users' perceptions of the platform's utility. In essence, when users encounter a variety of programs and films available on Netflix, they are more inclined to perceive Netflix as a beneficial and relevant entertainment solution that caters to their diverse entertainment preferences.…”
Section: Wwwjournalmabisorg 15mentioning
confidence: 99%
“…These results indicated sufficient manipulation effects of the video framing. Furthermore, since perceived video quality has been found as a critical factor that alters viewers’ reactions to a video (Park et al, 2016), to ensure the comparable quality of the three videos, perceived video quality was examined (1 = very poor; 5 = very good). The results demonstrated that video quality was not significantly different across the three videos (Kruska-Wallis test, p = .66).…”
Section: Methodsmentioning
confidence: 99%
“…TAM sangat baik digunakan untuk menjelaskan penerimaan seseorang terhadap suatu teknologi dimana penelitian Davis dikatakan variabel perceived usefulness adalah faktor utama bagi seseorang untuk memakai suatu teknologi yang fokus pada praktikalitas teknologi. Penelitian terdahulu telah membahas beberapa faktor yang mempengaruhi value yang dirasakan seseorang terhadap aplikasi streaming film (Park, Kang, & Zo, 2016) salah satu faktor tersebut adalah perceived usefulness yang dinilai paling berpengaruh pada keputusan seseorang untuk mengadopsi teknologi, penelitian Natarajan, Balasubramanian, & Kasilingam, (2018) menemukan perceived usefulness berpengaruh positif terhadap intention to use. Berhubungan dengan TAM Davis, F.D, (1989) juga mengatakan bahwa perlu untuk mengukur nilai intrisik dari suatu layanan sehingga pada pengembangan model penelitian lanjutan oleh Kim et al (2016) dan Tang, Zhang, & Akram, (2019) terdapat variabel perceived enjoyment untuk mengukur nilai intrisik diluar nilai instrumental begitu juga pada penelitian ini.…”
Section: Gambar 3 Pelanggan Streaming Netflix Indonesia 2017-2020unclassified
“…Perceived Enjoyment menjadi salah satu variabel yang sering digunakan untuk menjelaskan fenomena bahwa terdapat suatu nilai intristik pada sebuah teknologi terlebih dibandingkan dengan produk fisik karena pada teknologi dalam hal ini aplikasi fokus untuk memberikan inner spiritual needs dan pada beberapa penelitian terdahulu perceived enjoyment mempengaruhi usage intention secara positif (Tang, Zhang, & Akram, 2019). Selain itu perceived enjoyment dinilai lebih relevan dalam menganalisa penerimaan aplikasi hiburan karena bersifat hedonic system dengan kata lain menyediakan niliai self-fulfilling kepada penggunanya (Park, Kang, & Zo, 2016). Pada penelitian ini peneliti mendefinisikan perceived enjoyment sebagai nilai intristik diluar nilai instrumental aplikasi streaming film Netflix yang menjadi faktor pendorong secara independen untuk dapat menarik konsumen berlangganan layanan aplikasi streaming film Netflix.…”
Section: Tinjauan Pustaka 121 Perceived Enjoyment Terhadap Perceived ...unclassified